Dynamics Analysis of the Escapement Mechanism based on the Quantization of Hairspring Stiffness - Shijia Chen; Xiang Gong; Baoyu Huang (Jixie chuandong)
The escapement mechanism is the most important element of a mechanical watch movement with a complicated motion， though little is known about it. A dynamics Finite Element model of escapement mechanism is established，and based on the real micrograin structure of the key elastic element in the mechanism, the elastic properties of the hairspring are quantitatively calculated. The model is able to predicts the stress state of the parts of escapement speed regulating mechanism during the working process, which is consistent with ROLLAND simulation results. At the same time, the influence of the pendulum oscillation amplitude on the instantaneous daily rate is predicted and compared with the experimental data, it has good precision to some extent, the simulation results are in line with Airy Theorem. This model could be used to provide useful support in order to optimize the structure of the domestic mechanical watch movement in the future.